2019
DOI: 10.1111/acer.14119
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Evaluating the Association Between Alcohol Outlet Density and Violent Crime

Abstract: Background: The objective of this analysis was to compare measurement methods-counts, proximity, mean distance, and spatial access-of calculating alcohol outlet density and violent crime using data from Baltimore, Maryland.Methods: Violent crime data (n = 11,815) were obtained from the Baltimore City Police Department and included homicides, aggravated assaults, rapes, and robberies in 2016. We calculated alcohol outlet density and violent crime at the census block (CB) level (n = 13,016). We then weighted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
9
1
Order By: Relevance
“…The primary contributions of this article are the novel application of routine activity theory and spatial access methods used to calculate alcohol outlet access and violent crime exposure. In particular, previous work by study authors and others has shown that spatial access methods are more sensitive, precise, and stable than commonly-used counts of alcohol outlets and crime (Grubesic et al, 2016, Trangenstein et al, 2018). Other strengths of this analysis are using CBGs as the unit of analysis instead of census tracts, which reduces aggregation bias by avoiding averaging across larger, more heterogeneous areas.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The primary contributions of this article are the novel application of routine activity theory and spatial access methods used to calculate alcohol outlet access and violent crime exposure. In particular, previous work by study authors and others has shown that spatial access methods are more sensitive, precise, and stable than commonly-used counts of alcohol outlets and crime (Grubesic et al, 2016, Trangenstein et al, 2018). Other strengths of this analysis are using CBGs as the unit of analysis instead of census tracts, which reduces aggregation bias by avoiding averaging across larger, more heterogeneous areas.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, we calculated each SAI by summing the inverse distance from each CBG centroid to the 10 nearest outlets (Sacks et al, 2016). We did not restrict distance to the CBG borders to find the 10 closest outlets, and a set size of 10 outlets will smooth over three CBGs on average (Trangenstein et al, 2018). The final SAIs measured the exposure of CBGs to alcohol outlets and weighted alcohol outlets that are located closer to the CBG centroid more heavily than those that were further away.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, bars may lure drinking drivers to social locations away from their homes, and they may harm others along the way. However, we measured outlet density using counts of alcohol outlets in an area, which can introduce measurement error . These results should be interpreted with caution, and we encourage future research with more robust designs in this area.…”
Section: Discussionmentioning
confidence: 99%